2009
DOI: 10.1007/s10840-008-9361-8
|View full text |Cite
|
Sign up to set email alerts
|

Ablating the ventricular insertion of atrio-fascicular Mahaim fiber: what selection criteria should we use?

Abstract: We reported a patient who underwent RF ablation of the distal insertion of an atrio-fascicular accessory pathway with decremental properties because of inability to map a suitable potential alongside the tricuspid annulus. Small, discrete potentials resembling those of purkinje fiber were found at right ventricular apex, all these potentials showed early activation during tachycardia preceding the QRS onset of various degrees. Pace mapping helped to localize the presumed main distal insertion of the atrio-fasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Mahaim pathways may be ablated along the atrial aspect of the tricuspid annulus (at the site of a high-frequency potential, shortest stimulus-to–pre-excitation interval, and/or greatest advancement of subsequent QRS complex by critically timed atrial extrastimuli during AVRT), 13 , 14 , 15 or at the ventricular insertion site identified by activation mapping. 16 In this case, the AP was initially ablated at its proximal insertion. Sixteen years later, antegrade conduction through the AP fiber persisted without recurrent antidromic AVRT.…”
Section: Discussionmentioning
confidence: 99%
“…Mahaim pathways may be ablated along the atrial aspect of the tricuspid annulus (at the site of a high-frequency potential, shortest stimulus-to–pre-excitation interval, and/or greatest advancement of subsequent QRS complex by critically timed atrial extrastimuli during AVRT), 13 , 14 , 15 or at the ventricular insertion site identified by activation mapping. 16 In this case, the AP was initially ablated at its proximal insertion. Sixteen years later, antegrade conduction through the AP fiber persisted without recurrent antidromic AVRT.…”
Section: Discussionmentioning
confidence: 99%
“…In case of AF or long AV fibers, the pathway potential may be recorded remote from the tricuspid annulus and close to the right ventricular apex ( Figure 4). If no pathway potential is recorded along the presumptive course of the fiber, identification of its distal insertion site in the right ventricle can guide CA 9,14 . This site is generally identified by the earliest local bipolar ventricular activation preceding the ECG delta wave with a concomitant steep QS complex morphology in the unipolar recording.…”
Section: Catheter Ablationmentioning
confidence: 99%